Batteries: Metamorphosis of Seaweeds into Multitalented Materials for Energy Storage Applications (Adv. Energy Mater. 19/2019). Issue 19 (16th May 2019) - Shin, Myoungsoo; Song, Woo‐Jin; Han, Jung‐Gu; Hwang, Chihyun; Lee, Sangyeop; Yoo, Seokkeun; Park, Sewon; Song, Hyun‐Kon; Yoo, Seungmin; Choi, Nam‐Soon; Park, Soojin
Abstract : In article number1900570, Seungmin Yoo, Nam‐Soon Choi, Soojin Park and co‐workers demonstrate a seaweed‐extracted biomaterial for use as lithium‐ion battery components. It is utilized as a separator membrane and as a binder for use alongside Mn‐based cathode materials. The resultant full cells demonstrate highly stable cycling performance (84%) even at high‐voltage operation (3.5–5.0 V) under high temperature (>55 °C) at a high charge‐/discharge‐rate (1 C/1 C).